Expressionists Kandinsky, Münter and The Blue Rider - Sidlina, Natalia; Barton, Genevieve; Borkhardt, Sebastian 1984-; Christensen, Emily ca. 20./21. Jh; Grasselli, Anne; Leimer, Miriam; De Mille, Charlotte; Mühling, Matthias 1968-; Obler, Bibiana K. (Yale University Press, 2024)
"The story of the friendships that made modern art. Brought together in the UK for the first time in 80 years, this exhibition book offers unprecedented access to the landmark exhibition's collection of masterpieces. Expressionists is a story of friendships told through art – the groundbreaking work of a circle of friends and close collaborators known as The Blue Rider. In the early twentieth century they came together to form, in their own words, ‘a union of various countries to serve one purpose’ – to transform modern art. Rallying around Wassily Kandinsky and Gabriele Münter these highly individual artists experimented with colour, sound and light, creating astonishingly bold and vibrant art – from Alexander Sacharoff’s freestyle performance to Gabriele Münter’s experimental photography, from Franz Marc’s innovative use of colour to the dramatic paintings of Marianne Werefkin. In-depth investigations of major themes and a wide variety of spotlight essays provide an intimate and illuminating window into a remarkable artistic group: their travels and techniques, their interests and sources of inspiration, and the relationships that bound them together."
Published in the occasion of the exhibition of the same title, held at The Eyal Ofer Galleries,Tate Modern, London, 25 April-20 October 2024
Keywords: Der Blaue Reiter; Geschichte 1911-1914; Kunst; Expressionismus; Blaue Reiter (Group of artists); Expressionism (Art) / Germany / Exhibitions; Art, German / 20th century / Exhibitions; Ausstellungskatalog -- The Eyal Ofer Galleries, Tate Modern -- 25.04.2024-20.10.2024 -- London